Infant onset systemic lupus erythematosus presenting as nephrotic syndrome - Pouneh Dokouhaki; Assel Rakhmetova; Abdullah Alabbas (Society of Diabetic Nephropathy Prevention, 2018)
Background: Membranous nephropathy (MGN) is one of the most common glomerular disease seen among adults. However, it is a rare histological presentation in pediatric population. In contrast to MGN in adults where primary form is known to be the leading subtype of the disease, secondary cause is more prevailing in children. Case Presentation: We describe a case of an infant presenting with nephrotic syndrome (NS) and negative serology work-up. Kidney biopsy showed the picture of severe diffuse MGN confirmed by light, immunofluorescence and electron microscopy studies. "Full-house" pattern by immunofluorescence, numerous well-demarcated sub-epithelial deposits and tubuloreticular inclusions strongly suggested type V lupus nephritis. Conclusions: NS due to MGN is rarely seen in infancy. Secondary causes such as autoimmune disease or systemic infection need to be considered for appropriate management.